Microsoft Excel 2010 on demand - Johnson, Steve, 1961- (Que Pub., 2010)
What you need, when you need it! Need answers quickly? Microsoft Excel 2010 on Demand provides those answers in a visual step-by-step format. We will show you exactly what to do through lots of full color illustrations and easy-to-follow instructions. Includes Workshops MCAS Exam Prep More than 500 Essential Excel Tasks Inside the Book • Create workbooks more efficiently using the improved Ribbon interface • Use data-analysis tools and techniques for better decision making • Use organizing, processing, and presenting tools to create and analyze data • Integrate data from external sources and add hyperlinks • Use conditional formatting and Sparklines to visualize results • Add impact to your data with PivotTable and PivotChart reports • Organize information and add impact with clip art, SmartArt diagrams, tables, and charts • Use SharePoint to collaborate and share documents • Use the Excel Web App to view and edit documents in a browser • Prepare for the Microsoft Certified Application Specialist (MCAS) exam Bonus Online Content Register your book at queondemand.com to gain access to: • Workshops and related files • Keyboard shortcuts.